2020
DOI: 10.1177/0008125620914989
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leader or Narcissist? How Grandiose Narcissists Can Create and Destroy Organizations and Institutions

Abstract: Transformational leaders challenge the status quo, provide a vision of a promising future, and motivate and inspire their followers to join in the pursuit of a better world. But many of these leaders also fit the American Psychiatric Association classification for narcissistic personality disorder. They are grandiose, entitled, self-confident, risk seeking, manipulative, and hostile. This article reviews the literature on narcissism and shows how what we think of as transformational leadership overlaps substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 46 publications
0
24
1
1
Order By: Relevance
“…This is important because once in positions of authority, grandiose narcissists have also been found to make riskier decisions and jeopardize their institutions ( O'Reilly & Chatman, 2020 ). The results here may help explain why this happens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important because once in positions of authority, grandiose narcissists have also been found to make riskier decisions and jeopardize their institutions ( O'Reilly & Chatman, 2020 ). The results here may help explain why this happens.…”
Section: Discussionmentioning
confidence: 99%
“…However, research has also shown that grandiose narcissists' propensity to pursue their own interests can jeopardize the organizations and institutions they lead (e.g., Brunell et al, 2008 ; Nevicka et al, 2018 ). Several recent review papers have documented this danger (e.g., Braun, 2017 ; Campbell et al, 2011 ; Landay et al, 2019 ; O'Reilly & Chatman, 2020 ). Because numerous studies have shown a wide range of negative organizational outcomes of narcissism, we focused on the specific aspects of narcissism that might create such effects and attempt to show how these particular attributes lead to poor decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Narcissistic leadership is a leadership style, which is "principally motivated by leaders own egomaniacal needs and beliefs, superseding the needs and interests of the constituents and institutions they lead" (Rosenthal and Pittinsky, 2006, p. 631). Therefore, narcissistic leaders pursue their self-interest rooted in their self-egomaniacal beliefs (O'Reilly and Chatman, 2020;Ouimet, 2010).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Bass (1990), Yukl (1989) and Yukl et al (2002) provide a review of leadership behaviours. However, they fall broadly, with some overlaps, into the following categories: stewardship (Hernandez, 2008), transactional (Hackman et al, 1992), transformational (Hackman et al, 1992; Piccolo and Colquitt, 2006), authoritarian (Kiazad et al, 2010), charismatic (Conger et al, 2000; De Hoogh and Den Hartog, 2009), narcissistic (Chatterjee and Hambrick, 2007; O’Reilly and Chatman, 2020; Rosenthal and Pittinsky, 2006), autocratic (De Hoogh and Den Hartog, 2009) and heroism (Allison et al, 2017).…”
Section: Leader Performancementioning
confidence: 99%